2019
DOI: 10.1186/s13019-019-0836-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolated right atrial rupture from blunt trauma: a case report with systematic review of a lethal injury

Abstract: BackgroundIsolated right atrial rupture (IRAR) from blunt chest trauma is rare. There are no physical exam findings and non-invasive testing specific to the condition, which result in diagnostic delays and poor outcomes. We present a case of IRAR along with a systematic review of similar cases in the literature.Case reportA 23-year-old male presented following a motor vehicle accident (MVA). He was bradycardic and hypotensive during transportation; and required intubation. There were contusions along the right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…3 The mechanism for IRAR in our case is unclear but is likely related to hydraulic and deceleration forces potentially occurring at a particular moment in the cardiac cycle during the patient's fall. 3 Comotio cordis, for example, requires a blow to the heart at a very specific period during cardiac repolarization. Such a temporal coincidence may also be required in RA rupture but can only be hypothesized.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…3 The mechanism for IRAR in our case is unclear but is likely related to hydraulic and deceleration forces potentially occurring at a particular moment in the cardiac cycle during the patient's fall. 3 Comotio cordis, for example, requires a blow to the heart at a very specific period during cardiac repolarization. Such a temporal coincidence may also be required in RA rupture but can only be hypothesized.…”
Section: Discussionmentioning
confidence: 84%
“…2e4 RA rupture was reported to have occurred in 35 of 273 cases of cardiac rupture in a series of cases of nonpenetrating cardiac trauma by Parmley et al 2 Isolated right atrial rupture (IRAR) is a rare injury, most commonly resulting from blunt chest trauma. Maraqa et al 3 cited an incidence of IRAR of 0.2% to 0.5%. 3 In their review of reported cases since 1955, they identified 75 patients with IRAR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations